The working narrative: analysis of linguistic structures and styles in life storytelling on social media - Humphrey, Michael, author; Plaisance, Patrick, advisor; Long, Marilee, committee member; Anderson, Ashley, committee member; Sloane, Sarah, committee member; Mason, Kate, committee member (Colorado State University. Libraries, 2017)
The stories we tell ourselves, and others, define us. What does that mean when we enter digital life and populate social media networks? In this dissertation, I examine the linguistic structures and styles of content created by people who are specifically prompted to tell a story from their lives. The study focuses on two distinct types of storytelling social media platforms: Cowbird is an self-mediatizing, open site that primes users with life story cues and prompts them to "Tell a story," while Humans of New York is a filtered, gated-mediatized platform run by one curator who posts pictures and short life narratives on Facebook, Tumblr, his own blog and several other social platforms. I sought to find distinct and/or common narrative structural and stylistic characteristics of the content. Using a combination of Quantitative Content Analysis and Linguistic Inquiry and Word Count (Pennebaker et al., 2007; Pennebaker et al., 2015), this project includes three related studies that begin with basic questions about narrative structures and concludes with two factor analyses of latent linguistic variables. On Cowbird, the latent variables internal vs. external focus created two styles of storytelling, regardless of the structure of the stories. Humans of New York, on the other hand, had its own style that complicated the role of singular first-person in the narratives. I suggest the overarching phenomenon in this data is what I've termed a working narrative, which is in flux, performative and filtering information in accordance with present goals, either to be encoded to long-term memory or forgotten. This suggests a model, the Digital Self Memory System, that combines insights from Autobiographical Memory (Conway & Pleydell-Pearce, 2000) and the Infosphere (Floridi, 2014). I conclude with a discussion about the philosophical implications of the working narrative in light of current and future technological affordances.